Unveiling the fungal mycobiota present throughout the cork stopper manufacturing process - Barreto, Maria C; Houbraken, Jos; Samson, Robert A; Brito, Dulce; Gadanho, Mário; San Romão, Maria V (FEMS Microbiology Ecology, 2012)
A particular fungal population is present in the main stages of the manufacturing process of cork discs. Its diversity was studied using both dependent (isolation) and independent culture methods (denaturing gel gradient electrophoresis and cloning of the ITS1-5.8S-ITS2 region). The mycobiota in the samples taken in the stages before and after the first boiling seems to be distinct from the population in the subsequent manufacturing stages. Most isolated fungi belong to the genera Penicillium, Eurotium and Cladosporium. The presence of uncultivable fungi, Ascomycota and endophytes in raw cork was confirmed by sequencing. The samples taken after the first boiling contained uncultivable fungi, but in a few samples some isolated fungi were also detected. The main taxa present in the following stages were Chrysonilia sitophila, Penicillium glabrum and Penicillium spp. All applied techniques had complementary outcomes. The main factors driving the shift in cork fungal colonization seem to be the high levels of humidity and temperature to which the slabs are subjected during the boiling process.
Keywords: Biodiversity; cloning; Cork; denaturing gel electrophoresis; Denaturing Gradient Gel Electrophoresis; DNA; Fungal; Fungal: genetics; fungi; Fungi: classification; Fungi: isolation & purification; humidity; Industry; Metagenome; mycobiota diversity; Penicillium; Penicillium: classification; Penicillium: isolation & purification; phylogeny; Plant Bark; Plant Bark: microbiology; Portugal; Quercus; Quercus: microbiology; Ribosomal Spacer; Ribosomal Spacer: genetics; Spain; Temperature; uncultivable fungal species